2020
DOI: 10.3390/ijerph17051670
|View full text |Cite
|
Sign up to set email alerts
|

The Agglomeration of Manufacturing Industry, Innovation and Haze Pollution in China: Theory and Evidence

Abstract: Haze pollution in China is a serious environmental issue, which does harm both to people’s health and to economic development. Simultaneously, as an important industrial development law, agglomeration may result in the increased concentration of manufacturing firms and, consequently, an increase in haze pollution. However, the positive externalities of agglomeration can also improve the efficiency of regional innovation, which curbs haze pollution. In this paper, we construct both theoretical and empirical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…On the other hand, it can also increase the concentration of enterprises. The expansion of the production scale of enterprises will cause an increase in pollutant emissions and energy consumption in the regions, generating negative externalities on eco-innovation [33,36]. Besides, as the agglomeration deepens, the number and scale of enterprises continue to increase.…”
Section: Theoretical Framework Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it can also increase the concentration of enterprises. The expansion of the production scale of enterprises will cause an increase in pollutant emissions and energy consumption in the regions, generating negative externalities on eco-innovation [33,36]. Besides, as the agglomeration deepens, the number and scale of enterprises continue to increase.…”
Section: Theoretical Framework Analysismentioning
confidence: 99%
“…The reason for the generation of the negative externalities is that manufacturing agglomeration will increase the concentration of enterprises in the clustering regions, and the expansion of the economic production scale of enterprises will cause more environmental pollution and energy consumption, worsening the regional ecological conditions [35]. Liu et al [36] found that manufacturing agglomeration would intensify haze pollution. Yuan et al [33] indicated that manufacturing agglomeration would accelerate the consumption of resources and energy.…”
Section: Introductionmentioning
confidence: 99%
“…When encountering environmental issues, the positive externalities bring benefits to pollution abatement in two aspects—on the one hand, agglomeration can reduce firms' abatement cost; on the other hand, agglomeration can increase firms' abatement willingness. The positive externalities of economic agglomeration can induce the generation of new knowledge and technologies, as well as the transmission of information and skills, through intermediate input sharing, labor pooling and knowledge spillover (Chen et al., 2020; Liu et al., 2020; Zhou et al., 2019), which could motivate green innovation and lower the abatement cost. The agglomeration of industrial activities can facilitate centralized treatments of pollutants, achieve scale effects in pollution abatement and reduce the cost (Copeland & Taylor, 2004; Zhou et al., 2019).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Meanwhile, the positive and negative externalities of spatial agglomeration play an important role in the performance of environmental regulation. The positive externalities of agglomeration offer sufficient conditions for environmental regulation to play its role by lowering the compliance cost, motivating firms to adopt clean technologies and improve environmental efficiency (Liu et al., 2020). Whereas excessive agglomeration leads to increased resources and environmental load within limited areas and aggravate environmental deterioration (Han et al., 2018), then gives rise to stricter enforcement of environmental governance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, other scholars have explored the migration characteristics and models and mechanisms [19] of manufacturing enterprises from the perspectives of industry classification [20] and industry agglomeration [21]. Since 2015, researchers have tended to focus on the mechanisms affecting the location of newly built manufacturing enterprises, environmental impacts (carbon emissions and smog) [22], and the relationship among producer services [23].…”
Section: Introductionmentioning
confidence: 99%